The Illuminated Rumi - Jalal al-Din Rumi, 1207-1273, author 561422; Barks, Coleman, translator 534697; Green, Michael, 1943-, illustator 561424 (New York : Broadway Books, 1997)
"In the mid-thirteenth century, in a dusty marketplace in Konya, Turkey, a city where Muslim, Christian, Hindu, and Buddhist travelers mingled, Jelaluddin Rumi, a popular philosopher and scholar, met Shams of Tabriz, a wandering dervish. Their meeting forever altered the course of Rumi's life and influenced the mystical evolution of the planet. The bond they formed was everlasting - a powerful transcendent